Metatropic dysplasia in children - Akhter, S; Rahman, SA; Momen, MA; Karim, ME; Kawser, CA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):93-7. The abstract of this article is available on the PubMed website